KLINEFELTER SYNDROME AND OTHER SEX CHROMOSOMAL ANEUPLOIDES IN THE R. OF NORTH MACEDONIA - Plasheski, Toso; Bitoska, Iskra; Mihajlovska, Dzuliana; Jovanovska Mishevska, Sasha; Markovic, Snezana; Plaseska-Karanfilska, Dijana; Noveski, Predrag (Journal of Morphological Sciences, 2022)
Chromosomal anomalies are frequent in male infertility with an incidence of 5.8%, higher than the incidence in general fertile population of 0.5%. Klinefelter syndrome (47, XXY) is the most common disorder of sex chromosomes in humans found in 11% of patients presenting with azoospermia and in 0.7% of patients presenting with oligozoospermia. Boys with 47,XXY are indistinguishable from other boys with normal karyotypes and are often detected when they are evaluated for infertility later in life. Other sex chromosomal anomalies occur less frequently in infertile men.It is considered that many of the 47, XYY men are fertile and this aneuploidy occurs rarely among infertile men. Cases of 46, XX males have also been reported. Molecular analysis shows that most of the 46, XX men have a translocation of the SRY(sex-determining gene) from the Y chromosome on the X chromosome. In our study we analysed the karyotypes of infertile men and identified 39 infertile men with sex chromosomal aneuploidies and Y chromosome micro-deletions. Most of 39 patients had Klinefelter syndrome (31/39 or 79.5%), 4 men had 46,XYY syndrome and 4 had 46,XX syndrome. All detected cases of chromosome aneuploidies were confirmed by cytogenetic analysis.    Keywords : Klinefelter syndrome, male infertility, chromosomal aneuploidy. https://doi.org/10.55302/JMS2251113p